Isim: Pengobatan dalam Naskah Sunda Koleksi Naskah Obat Museum Sri Baduga (07.123) - Agus Heryana (Jumantara: Jurnal Manuskrip Nusantara, 2023)
Isim in the Sundanese tradition or rajah (Javanese, Malay/Indonesian) is related to the science of kanuragan arising from the use of magical objects, namely objects written with Arabic inscriptions or certain symbols for certain purposes as well. Isim is believed by its users to have supernatural powers that are beneficial to their interests. In traditional medicine, apart from medicinal plants or herbs, isim is also used as part of the treatment. Sundanese medicinal manuscripts in the collection of the Sri Baduga Museum, West Java Province, inform that there is treatment through the use of isim. In addition to describing various diseases and methods of treatment, the Sundanese medical texts are also accompanied by pictures of isim. It is this image of isim that becomes the object of the problem for understanding the form and function of isim text in its medical system. The aims of the research are (1) to know the form and function of the isim, and (2) to understand the content of the isim. The analytical descriptive method or content analysis is the choice for dissecting drug manuscripts considering the method used begins with collecting data, compiling or classifying it, analyzing and interpreting it. The research results show that there is almost no connection between occult writing and the disease itself. There is no need for reasoning or rationalization to look for a relationship between the disease being suffered and the medical terms, except for the strength to believe in what one is doing. Isim will not function without trust in the isim.